2007
DOI: 10.1088/1367-2630/9/8/264
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic transport in ferromagnet–superconductor–ferromagnet trilayers with arbitrary orientation of magnetisations

Abstract: Transport phenomena in clean ferromagnet-superconductor-ferromagnet (FSF) trilayers are studied theoretically for a general case of arbitrary orientation of in-plane magnetizations and interface transparencies. Generalized expressions for scattering probabilities are derived and the differential conductance is computed using solutions of the Bogoliubov-de Gennes equation. We focus on size and coherence effects that characterize ballistic transport, in particular on the subgap transmission and geometrical oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Following the calculations of Refs. 32,33,34,35 , we express the normalized conductance of our system when a voltage eV is symmetrically applied to the junction with eV /2 in F L and (−eV /2) in F R as:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Following the calculations of Refs. 32,33,34,35 , we express the normalized conductance of our system when a voltage eV is symmetrically applied to the junction with eV /2 in F L and (−eV /2) in F R as:…”
Section: Theorymentioning
confidence: 99%
“…Previous theoretical works have considered the MR in conventional (s-wave) F|S|F spin-valves for either exclusively P or AP configurations 33,34 , while recently Ref. 35 considered an arbitrary magnetization configuration. Here, we will investigate the influence of a d-wave superconducting order parameter on the MR, with particular emphasis on the role of zero-energy states.…”
Section: Theorymentioning
confidence: 99%
“…In most of the earlier works on tunnelling spectroscopy [97][98][99][100][101][102][103][104][105][106][107][108][109], it was found that the barrier thickness play a very significant role on the transport mechanism. However, the role of barrier thickness on spin transport is yet to be understood.…”
Section: A Spin Conductance Spectra At the F|ncsc Interfacementioning
confidence: 99%
“…Transport properties in several F|Singlet SC [97][98][99], F|Triplet SC [100][101][102][103][104][105] and F|NCSC [106][107][108][109] heterostructures had been studied earlier. However, the role of magnetization in spin transport, spin current [110][111][112][113][114][115] and its interplay with pair potential, magnetic field and RSOC of NCSC in F|NCSC|F SV is still need to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…These structures have been studied using quasiclassical approach in both diffusive 1,2,3,9,10,11,12,13 and clean 14,15,16 limits by solving Usadel 17 and Eilenberger 18 equations, respectively, and by solving the Bogoliubov-de Gennes equation. 6,19,20,21,22 In the case of parallel (α = 0) magnetizations, SFS junctions, 23,24 besides spin-singlet superconducting correlations, only odd triplet correlations with zero total spin projection exist. These correlations penetrate into the ferromagnet over a short length scale determined by the exchange energy.…”
Section: Introductionmentioning
confidence: 99%